2017
DOI: 10.1042/bsr20170114
|View full text |Cite
|
Sign up to set email alerts
|

Poly r(C) binding protein (PCBP) 1 expression is regulated by the E3 ligase UBE4A in thyroid carcinoma

Abstract: Thyroid cancer patients with high miR-490-3p inhibit translation of PCBP1 mRNA, whereas in patients with low miR-490-3p PCBP1 mRNA expression is high; however, the resultant protein is targeted for degradation through the proteasome. The objective of the present study was to evaluate the molecular mechanism that regulates post-translation degradation of poly r(C) binding protein (PCBP) 1 expression in thyroid cancer cells. Mass spectrometric analysis of PCBP1 immunoprecipitates from MG-132 treated TPC1 cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…Loss of PCBP1 is involved in various carcinogenesis [ 6 , 13 , 25 , 26 ]. Recently, PCBP1 has been shown as a negative regulator of thyroid carcinoma [ 44 ], a negative regulator of EMT related to metastasis in NSCLC [ 45 ], while PCBP1 expression is suppressed in peritoneal gastric cancer metastasis [ 46 ]. PCBP1 also can sensitize colorectal cancer to anti-cancer drug [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of PCBP1 is involved in various carcinogenesis [ 6 , 13 , 25 , 26 ]. Recently, PCBP1 has been shown as a negative regulator of thyroid carcinoma [ 44 ], a negative regulator of EMT related to metastasis in NSCLC [ 45 ], while PCBP1 expression is suppressed in peritoneal gastric cancer metastasis [ 46 ]. PCBP1 also can sensitize colorectal cancer to anti-cancer drug [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, E3 ubiquitin ligase UBE4A induced ubiquitination and degradation of PCBP1 in thyroid cancer, thereby decreasing the expression of PCBP1 protein. 16 TGF-β treatment in prostate cancer cells did not reduced the mRNA level of PCBP1, but it decreased the protein level of PCBP1 through inducing the poly-ubiquitination and degradation of PCBP1, thus resulting in the abnormal alternative splicing of CD44 and increasing the EMT. 17 In recent years, researchers have attempted to elucidate the multiple regulation of PCBP1 in tumorigenesis, development or metastasis, but the research about precise molecular mechanism was not very thorough.…”
Section: Introductionmentioning
confidence: 89%
“…65 Further research demonstrated that E3 ligase UBE4A was involved in the post-translation degradation of PCBP1 in thyroid cancer. 16 Of note, the expression of PCBP1 was significantly higher in non-small cell lung cancer tissues without lymph nodes metastasis compared with the tissues with lymph nodes metastasis. It might be correlated with TNM staging, lymph node metastasis (P < .001), and EMT-related proteins E-cadherin or vimentin.…”
Section: Pcbp1 Functions As a Tumor Suppressor In Most Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Under folate deficient conditions, hnRNP E1 translationally up-regulates this transcript leading to an increase of cell surface folate receptors which promotes folate up-take [69,70]. Numerous studies have linked hnRNP E1 to the process of tumorigenesis and metastasis, demonstrating that hnRNP E1 acts as a tumor suppressor in several cancer types [5,7,8,71,72]. Silencing of hnRNP E1 results in the transition of cells to a mesenchymal phenotype, an increase in cell motility and invasiveness, and the promotion of tumor formation and distant metastases [5,6,8].…”
Section: Hnrnp E1 As a Downstream Effector Of Tgf-β Signalingmentioning
confidence: 99%